Tourism-Based Community Empowerment of People with Disabilities - Kiki Irafa Candra; Yudan Hermawan; Tristanti; Eni Suyantri; Rudiana (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores a tourism village-based community empowerment model in Karangpatihan, a village with a significant population of people with intellectual disabilities, aiming to improve their economic and social welfare. Using an intrinsic case study approach with qualitative methods, informants were purposively selected, including the village head, Rumah Harapan managers, active programme participants, and their families. Data was collected through interviews, observation, and documentation, then analysed using Huberman's interactive model. The programme’s training in batik ciprat, handicraft making, and tourism management significantly improved outcomes. Participants’ income increased by 30%-40%, supported by sales of crafts and tourism roles. Socially, stigma against disabilities lessened as participants engaged in guiding tours and ticket management. Challenges included limited digital marketing innovation, insufficient training continuity, and low initial motivation. Recommendations include enhancing digital marketing through social media training, e-commerce platforms, and diversifying local products. This model demonstrates strong potential for replication as an inclusive and sustainable rural development strategy.